Project finance law and regulation in Tanzania: a critical analysis - Ngwembe, Geofrey P (Department of Commercial Law, 2018)
Long term finance schemes are, to a little extent, employed in Tanzania since major economic reforms which occurred in the 20th C. Shifting from public finance mechanism, the government of Tanzania have initiated mechanism such as PPP in order to instil private sector in engaging in several economic activities. As projects basis form of investment have been adopted in catering with developmental plans, especially in becoming an industrialized nation - Tanzania - by 2025, an effective legal and regulatory framework for project finance is crucial. Despite having PPP, Tanzania still faces several challenges, especially on its recognition and implementation, mainly, inadequate legal framework as project finance not only caters for PPP transactions, but also for private and public finance of projects, lack of specific regulatory body/division, as well as extensive government interference in projects. The lack of an effective legal and regulatory framework for project finance mechanism deters its success unless it is redressed, hence the purpose of this dissertation which is to ascertain and review project finance setting in Tanzania, experiences and lessons will be drawn from the UK and South Africa in determining the legal and regulatory framework of project finance in Tanzania, tackling of challenges within, and way forward in the incorporation of project finance mechanism as a new mechanism in Tanzania's jurisdiction.